2017
DOI: 10.1177/2399808317744779
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying relationships between land use and crime: A spatio-temporal analysis of small-area seasonal property crime trends

Abstract: Acknowledgements:We thank the Waterloo Regional Police Service for providing crime data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…For small‐area data, the most common prior distribution used to model residual spatial structure is the intrinsic conditional autoregressive distribution (ICAR), which borrows information from nearby areas to estimate a spatially smoothed risk surface (Besag et al ; see Section “Prior distributions”). With a temporal adjacency matrix, the ICAR prior distribution has also been applied to model nonlinear time trends (Richardson et al ; Quick et al ). Past studies applying Bayesian spatiotemporal models to small‐area crime data have analyzed violent crime and property crime over two years (Law et al ; ), burglary over 4‐ and 8‐year time periods (Li et al ; ), and police confidence over 36 quarters (Williams et al ).…”
Section: Introductionmentioning
confidence: 99%
“…For small‐area data, the most common prior distribution used to model residual spatial structure is the intrinsic conditional autoregressive distribution (ICAR), which borrows information from nearby areas to estimate a spatially smoothed risk surface (Besag et al ; see Section “Prior distributions”). With a temporal adjacency matrix, the ICAR prior distribution has also been applied to model nonlinear time trends (Richardson et al ; Quick et al ). Past studies applying Bayesian spatiotemporal models to small‐area crime data have analyzed violent crime and property crime over two years (Law et al ; ), burglary over 4‐ and 8‐year time periods (Li et al ; ), and police confidence over 36 quarters (Williams et al ).…”
Section: Introductionmentioning
confidence: 99%
“…A park is an appealing meeting place on a warm summer evening, but less so on a cold and windy winter night. In support of this, Quick et al (2017) found that, in warm seasons, crime rates are higher in areas dominated by parks, whereas in colder seasons, crime rates are higher in areas with nightlife. Corcoran, Higgs, Rohde and Chhetri (2011) found some evidence that the increase in city fires on warm days is greater in poor neighborhoods.…”
Section: The Effect Of Weather On the Spatial Distribution Of Crimementioning
confidence: 73%
“…Weather may affect the number of people who experience opportunities to commit crimes and the number who will be exposed to such crimes. However, changing weather does not necessarily impact overall crime rates; instead, it may rather lead to crimes being committed at alternative locations (Quick, Law, and Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have incorporated areal characteristics in the model to explain the varying levels of crime in space and time. They have linked changes of crime levels in relatively small areas to the characteristics of areal units such as predefined geographical neighborhood (Harries, Stadler, & Zdorkowski, 1984) census tract (Sorg & Taylor, 2011), or census block (Haberman, Sorg, & Ratcliffe, 2018; Quick, Law, & Li, 2017). Harries and colleagues (1984) tracked the level of assault by the economic status of the neighborhood in the city and found that low-status neighborhoods show a more distinct peak of assault in the summer.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Harries and colleagues (1984) tracked the level of assault by the economic status of the neighborhood in the city and found that low-status neighborhoods show a more distinct peak of assault in the summer. Quick et al (2017) studied how specific land use or the presence of certain facilities is related to the seasonal change of property crime and suggested that parks and eating and drinking establishments are related to additional seasonal variation of crime. Haberman et al (2018) also focused on how the effect of specific facilities on street robbery changes across seasons.…”
Section: Theoretical Backgroundmentioning
confidence: 99%